2003
DOI: 10.1007/s00122-003-1340-y
|View full text |Cite
|
Sign up to set email alerts
|

Sectional relationships in the genus Musa L. inferred from the PCR-RFLP of organelle DNA sequences

Abstract: The objective of this study was to construct a molecular phylogeny of the genus Musa using restriction-site polymorphisms of the chloroplast (cpDNA) and mitochondrial DNA (mtDNA). Six cpDNA and two mtDNA sequences were amplified individually in polymerase chain reaction (PCR) experiments in 13 species representing the four sections of Musa. Ensete ventricosum (W.) Ch. was used as the outgroup. The amplified products were digested with ten restriction endonucleases. A total of 79 restriction-site changes were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 26 publications
(32 reference statements)
4
24
0
Order By: Relevance
“…This contrasts strongly to the situation found in other plants. For example, PCR-RFLP analysis of mtDNA intronic regions has been used successfully to detect interspecific polymorphisms in Actinidia (Testolin and Cipriani 1997), Elymus (Sun 2002), Musa (Nwakanma et al 2003), Vasconcellea (Van Droogenbroeck et al 2004) and Houttuynia (Wei et al 2005), and even intraspecific polymorphisms in Quercus robur (Dumolin-Lapegue et al 1995), Actinidia deliciosa (Testolin and Cipriani 1997), Picea abies (Grivet et al 1999), Solanum tuberosum (Bastia et al 2001), Eucalyptus globulus (Vaillancourt et al 2004) and Buchloe dactyloides (Gulsen et al 2005). In a study of eight genotypes of Eucalyptus globulus, a mtDNA polymorphism was detected within 7960 bp of sequence space after screening only 36 primer pair-enzyme combinations (Vaillancourt et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…This contrasts strongly to the situation found in other plants. For example, PCR-RFLP analysis of mtDNA intronic regions has been used successfully to detect interspecific polymorphisms in Actinidia (Testolin and Cipriani 1997), Elymus (Sun 2002), Musa (Nwakanma et al 2003), Vasconcellea (Van Droogenbroeck et al 2004) and Houttuynia (Wei et al 2005), and even intraspecific polymorphisms in Quercus robur (Dumolin-Lapegue et al 1995), Actinidia deliciosa (Testolin and Cipriani 1997), Picea abies (Grivet et al 1999), Solanum tuberosum (Bastia et al 2001), Eucalyptus globulus (Vaillancourt et al 2004) and Buchloe dactyloides (Gulsen et al 2005). In a study of eight genotypes of Eucalyptus globulus, a mtDNA polymorphism was detected within 7960 bp of sequence space after screening only 36 primer pair-enzyme combinations (Vaillancourt et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The PCR-RFLP approach to study organellar genome diversity has been reported in many plants (Tsumura et al, 1995(Tsumura et al, , 1996Lakshmi et al, 2000;Parani et al, 2000Parani et al, , 2001Komatsu et al, 2001;Kishimoto et al, 2003;Nwakanma et al, 2003;Zhu et al, 2003;Asadi Abkenar et al, 2004Van Droogenbroeck et al, 2004;Ibrahim et al, 2007;Sehgal et al, 2008;Jena et al, 2009;Poczai et al, 2011). This work aimed at deciphering the polymorphism in the chloroplast and mitochondrial genomes in the Saccharum spp.…”
Section: Discussionmentioning
confidence: 99%
“…Specific chloroplast genes and/or intergenic spacers can be amplified (Taberlet et al, 1991;Demesure et al, 1995;Tsumura et al, 1995Tsumura et al, , 1996Dhingra and Folta, 2005;Heinze, 2007). The amplicons can be directly sequenced or restriction endonuclease digested (PCR-RFLP) or subjected to cleaved amplified polymorphic sequence (Tsumura et al, 1995(Tsumura et al, , 1996Lakshmi et al, 2000;Parani et al, 2000Parani et al, , 2001Komatsu et al, 2001;Kishimoto et al, 2003;Nwakanma et al, 2003;Zhu et al, 2003;Asadi Abkenar et al, 2004Van Droogenbroeck et al, 2004;Ibrahim et al, 2007;Sehgal et al, 2008;Jena et al, 2009;Poczai et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cheesman's classification provided a general framework for future studies on Musa taxonomy and was used for almost half a century without any significant modifications (De Langhe 2000). Furthermore, the Eumusa species of banana, which include modern cultivars, appear to be very diverse (Nwakanma et al 2003). Modern cultivated bananas, which have mostly triploid genomes, evolved from intra-and interspecific hybridization between two wild diploid species of Eumusa, M. acuminata Colla.…”
mentioning
confidence: 99%
“…Umali and Nakamura (2003) reported a single nucleotide polymorphic sequence (SNP) in the trnL-F intergenic spacer region of chloroplast DNA, that discriminates between M. acuminata (AA) cytoplasm from M. balbisiana (BB) cytoplasm, and used it to generate dCAPS (derived cleaved amplified polymorphic sequence) markers. Nwakanma et al (2003) also developed an PCR-RFLP marker system from ribosomal DNA internal transcribed spacers (ITS) for discriminating between the A and B genomes of Musa. Ude et al (2002aUde et al ( , 2002b the genetic characterization of banana cultivars from Brazil, while Onguso et al (2004) used RAPD markers to analyze the genetic relationships between Kenyan banana cultivars.…”
mentioning
confidence: 99%